Dessaturação de oxigênio durante a simulação de atividades de vida diária em pacientes após alta hospitalar pela COVID-19 - Zopelari, Livia Maria Petilli (Universidade Federal de São Carlos, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) caused by SARS-COV-2, can cause anything from an asymptomatic infection to a serious infection requiring hospitalization. The disease's impairments can be both respiratory and multisystemic, and in relation to respiratory impairments, arterial hypoxemia stands out, which can be present at rest or during exercise, as well as generating limitations in the performance of activities of daily living (ADL). Current researches found that patients after hospital discharge due to COVID-19 may present respiratory sequelae, however, studies that evaluated the presence of a drop in peripheral oxygen saturation (SpO2) during the simulation of an ADL circuit in patients after COVID-19 are still incipient. Objectives: To verify by telemonitoring the presence of oxygen desaturation during the simulation of an activity of daily living (ADL) circuit in patients after hospital discharge by COVID-19 and to compare SpO2 in ADL in patients with and without oxygen desaturation. Methods: This is an observational cross-sectional study, in which patients aged from 35 to 85 years were recruited after the 30th day of hospital discharge by COVID-19. Anamnesis and a simulation of an ADL circuit (randomized) were carried out, involving four activities: walking (ADL1), bathing and dressing (ADL2), sweeping the house (ADL3) and folding towels (ADL4) lasting 5 minutes each. All assessments were performed by telemonitoring and oxygen desaturation (fall in SpO₂ ≥ 4%) was monitored using a pulse oximeter. Results: 66 patients were evaluated, 28 female and 38 male, aged 54±10 years, BMI (Kg/m²) 31±5, median length of stay of 10 [5-17] days, PaO₂ of 67 [58-78} mmHg and SaO₂ of 93 [91-96] % at hospital discharge. Patients had 96 [95-98] % resting SpO₂ and resting HR 89±13 bpm at baseline. In the analysis all patients were normoxic at rest. Of the total number of patients, 29 (44%) had oxygen-induced desaturation in at least one ADL, while 37 (56%) did not, allowing the division into two groups of patients, desaturating group (GD) and non-desaturating group (GND). Regarding the groups, there was a significant difference between cardiovascular comorbidities and diabetes mellitus, in which group GD had a greater number of patients with these diseases than group GND. In addition, there was a significant difference between the groups for SpO2 immediately after ADL, and the GD group presented a greater number of individuals with SpO2 ≤ 90% than the GND in the activity of walking. Conclusion: It is concluded that a percentage of patients had oxygen desaturation in at least one ADL assessed by telemonitoring after hospital discharge by COVID-19. In addition, lower SpO2 values were observed immediately after ADLs and greater falls in the SpO2 delta during all ADLs for the desaturator group, as well as a greater number of patients with comorbidities.
Oxygen desaturation during simulation of activities of daily living in patients after hospital discharge due to COVID-19
Keywords: COVID-19; Hipoxemia; Atividade de vida diária; Telemonitorização; Hypoxemia; Activity of daily living; Telemonitoring; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar